The Baltic States: No End to the Crisis in Sight - Patricia Alvarez-Plata; Hella Engerer (Weekly Report, 2009)
The global financial crisis and the dramatic slump in private capital flows associated with it has particularly affected the economies of the Baltic countries. The real gross domestic product decreased in the first half of 2009 in Latvia by 18.8 percent, in Estonia by 15.7 percent and in Lithuania by 11 percent. In the run-up to the current crisis, these countries had a high percentage of bank-related capital inflows that was mostly used for the financing of very high current account deficits. Currently, due to their fixed currency exchange systems and due to the lack of a possibility to create fiscal momentum, the Baltic countries only have limited economic scope of action. The situation of the public budgets is particularly tense in Latvia. Early warning indicators point to an imminent currency crisis in Latvia. A devaluation would improve the competitiveness of the country, but due to the high amount of credits given in foreign currencies, it would lead to large-scale domestic credit failures. A strong devaluation could also have negative effects on the two other Baltic countries. The example of the Baltic States shows how problematic a development strategy that is based on a high degree of foreign capital inflows actually is.
Keywords: F3; 330; Baltic countries; Currency crisis